Assessment of the participation of students in physical activities during the pandemic of covid-19 - Bahtiri, Abedin; Tahiraj, Enver; Havolli, Jeton; Ilazi, Sherif; Begu, Bujar (VIREF Revista de Educación Física, 2023)
ABSTRACT Objective: Purpose of this study was to assess level of physical activity adolescents before and during pandemic of COVID_19. Methods: The research included 717 students, 422 females and 297 males, aged 10-15 years from the main regions of Kosovo. The research was conducted during June 2020 as in the previous months there were more stringent restrictions on movement during the day, while in June the restraint measures were released and most of the day the movement was free. An abbreviated version of the IPAQ-SF questionnaire was used. Results: The average body height of students aged 10-15 is 162.01cm, while bodyweight is 53.59kg. Students sit for an average of 2.79 hours a day. In terms of moderate physical activity, students are active 3.67 days a week and 32.85 minutes during the day. Students do a strenuous physical activity about 3 days a week (3.27), while during the day they do 25.45 minutes. Coclusion: Moderate and vigorous activities do not meet the required criteria, so it can be said that Kosovar children during the pandemic did a below-average physical activity. Of course, the Covid-19 pandemic has resulted in decreased student physical activity given movement limitations and the development of online learning which has reduced mobility requirements.